The Effect of the Three Lines of Defense Model on the Performance of State-Owned Enterprises Moderated by the Audit Committee - Jamaludin Iskak; Mochamad Muslih (GoAcademica Research & Publishing, 2022)
This study's objective is to examine the impact of adopting three lines of defense on the performance of State-Owned Enterprises (BUMN) in Indonesia, as moderated by an audit committee. The method employed is quantitative. In Indonesia, the population consists of State-Owned Enterprises. Practitioners, observers, and academics compose the sample. The utilized data is primary data. An online questionnaire was used to collect data. 128 (one hundred twenty-eight) individuals completed an online questionnaire that was sent via email and Whatsapp. The results indicate that line 1 (risk owner) has a positive effect on firm performance, line 2 (risk manager) has a negative effect on firm performance, and line 3 (Internal Audit Unit) has no effect on firm performance. The Audit Committee does not moderate the influence of line 3 (Internal Audit Unit) on firm performance, while it moderates the influence of line 2 (risk management unit) on firm performance.